Saiteja Mandalapu, Sandeep Viswanadhula , Thanikaiselvan V, Sakshi Pate, Amirtharajan R - Saiteja Mandalapu, Sandeep Viswanadhula , Thanikaiselvan V, Sakshi Patel, Amirtharajan R (International Journal of Advanced Science and Technology, 2020)
It is the day and age where digital media and wireless communications have some of the most important role in the data transmission. So, the security of the information and user’s privacy became a prime factor. This has led to the increase in the need of easy and effective methods to secure the data. Image encryption is one of the important and key factor in ensuring security since it is used in many domains like multimedia, defence and medicine. The beauty of image encryption is that there is no direct and absolute relation between original image and cipher image, but it is very easy to obtain the original image from encrypted or cipher image. This paper discuss about using interpolation with hybrid chaotic maps, scrambling and Deoxyribonucleic Acid (DNA) encryption. Hybrid chaotic maps together with scrambling provide an excellent randomness to the encryption while DNA is for diffusion moreover DNA computing provides characteristics like large storage capacity, high parallelism, and low energy consumption. By using these concepts together we can provide a reliable encrypted image that is prone to the attacks. The encryption methodology and results obtained shows the efficiency of the technique.